Congenital Myasthenic Syndrome with Agrin Mutations - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Newcastle University, UK, and Hopitaux de Paris, France, report 5 patients from 3 unrelated families with a strikingly homogeneous clinical entity combining congenital myasthenia with distal muscle weakness and atrophy resembling a distal myopathy.